PENGARUH EDUKASI VULVA HYGIENE TERHADAP LAMA PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI KLINIK HELEN TARIGAN KOTA MEDAN TAHUN 2022 - Rini Debora Silalahi; Reisy Tane; Regina Vidya Trias Novita (Jurnal Penelitian Keperawatan Medik, 2022)
Based on the above background and the problems above, the researchers are interested in taking the title "the effect of vulvar hygiene education on the duration of perineal wound healing in postpartum women at the Helen Tarigan clinic, Medan city in 2022". Analyzing vulvar hygiene education, analyzing perineal wound healing time, analyzing the effect of vulvar hygiene education on perineal wound healing time in postpartum mothers at the Helen Tarigan clinic, Medan city in 2022. This study uses a quantitative research design with non-experimental research. From the results and discussion of the study, the effect of vulvar hygiene education on the duration of perineal wound healing in postpartum mothers at the Helen Tarigan Clinic, Medan City in 2022. The results of the study showed that of the 30 respondents, the majority aged 20-35 years were 24 respondents (80.0%), 23 respondents were knowledgeable with good education (76.7%), 7 people had poor educational knowledge (23.3%). Fast wound healing as many as 17 people (56.7%), normal as many as 7 people (23.3%), and Old as many as 6 people (20.0%). Spearmen rank test results with p value 0.00 > a: 0.03 where Ho is rejected and Ha is accepted. Spearmen rank test results with p value 0.00 > a: 0.03 where Ho is rejected and Ha is accepted. So the conclusions that can be obtained from this study are: there is a significant effect between vulvar hygiene education on the duration of perineal wound healing in postpartum women at the Helen Tarigan clinic, Medan city in 2022.